CX3CL1 Worsens Cardiorenal Dysfunction and Serves as a Therapeutic Target of Canagliflozin for Cardiorenal Syndrome - Cankun Zheng; Wanling Xuan; Zhenhuan Chen; Zhenhuan Chen; Rui Zhang; Xiaoxia Huang; Yingqi Zhu; Siyuan Ma; Kaitong Chen; Lu Chen; Mingyuan He; Hairuo Lin; et al. (Frontiers Media S.A., 2022)
The prognosis of cardiorenal dysfunction induced by diabetes mellitus (DM), which belongs to cardiorenal syndrome type 5, is poor and its pathogenesis remains elusive. We have reported that CX3CL1 exacerbated heart failure and direct inhibition of CX3CL1 improved cardiac function. Emerging evidence supports that CX3CL1 is involved in renal impairment. Here we attempt to clarify whether CX3CL1 might be a therapeutic target for cardiorenal dysfunction in diabetes. We found that cardiac and renal CX3CL1 protein levels were significantly increased in both streptozotocin-induced diabetic mice and in non-obese diabetic mice, and that hyperglycemia led to persistent CX3CL1 expression in the heart and kidneys even after it was controlled by insulin. In cultured cardiac and renal cells, soluble CX3CL1 accelerated mitochondrial-dependent apoptosis via activation of the RhoA/ROCK1-Bax signaling pathway and promoted fibrosis through cellular phenotypic trans-differentiation mediated by the TGF-β/Smad pathway. In the two diabetic mouse models, knockout of CX3CL1 receptor CX3CR1 or treatment with an CX3CL1 neutralizing antibody significantly improved cardiorenal dysfunction by inhibiting apoptosis, mitochondrial dysfunction, and fibrosis. Moreover, sodium glucose cotransporter 2 inhibitor canagliflozin significantly downregulated cardiac and renal CX3CL1 expression and improved cardiorenal dysfunction. These findings indicate that CX3CL1 could be a new therapeutic target for diabetes-induced cardiorenal dysfunction.